2004
DOI: 10.1063/1.1784551
|View full text |Cite
|
Sign up to set email alerts
|

Spectral emissivity and temperature measurements of selective bodies using multiband fiber-optic radiometry

Abstract: A passive method of measuring the spectral emissivity and the temperature of materials in the mid- and the far IR is described both in theory and experiment. Theoretical evaluation and real measurements (spectral emissivity and temperature) of selective bodies utilizing IR transmitting silver halide optical fibers are presented. We carried out the theoretical evaluation and measurements for a multiband fiber-optic radiometer, which consists of a silver halide (AgClBr) infrared transmitting fiber, a dual-band c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It is well known that the spectral emissivity of a target is very difficult to be determined accurately because the spectral emissivity is very sensitive to the change of wavelength and temperature [1,[3][4][5][6]. Even for a definite wavelength and a definite temperature, previous experimental work has demonstrated that the surface roughness [1,7,8], emission angle [9,10], surface oxidization [7,[10][11][12][13][14], and the presence of pollutants [3] on the specimen surface can sometimes greatly influence the spectral emissivity. That is, any change of these conditions can make the spectral emissivity reported in the literature become less valuable or sometimes even valueless.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the spectral emissivity of a target is very difficult to be determined accurately because the spectral emissivity is very sensitive to the change of wavelength and temperature [1,[3][4][5][6]. Even for a definite wavelength and a definite temperature, previous experimental work has demonstrated that the surface roughness [1,7,8], emission angle [9,10], surface oxidization [7,[10][11][12][13][14], and the presence of pollutants [3] on the specimen surface can sometimes greatly influence the spectral emissivity. That is, any change of these conditions can make the spectral emissivity reported in the literature become less valuable or sometimes even valueless.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic behavior of spectral emissivity poses a great challenge in the use of radiation thermometers. Multispectral radiation thermometry (MRT) can be used to address the above challenges and has widely been used in many applications [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] to measure temperature, mainly targeting metallic surfaces. Effectiveness of this technique is greatly dependent on emissivity model used.…”
Section: Introductionmentioning
confidence: 99%
“…Surface oxidization is always travelling through the whole manufacture processes. Up to now, a great amount of work [2][3][4][5][6] has been made to clarify the effect of measurement angle, surface roughness, and wavelength on the spectral emissivity, whereas little work has been focused on the relationship between the spectral emissivity and the surface oxidization. Even for some common materials such as steel, the effect of surface oxidization on the spectral emissivity is not thoroughly studied, though great temperature measurement errors can sometimes be generated by the surface oxidization at an elevated temperature.…”
Section: Introductionmentioning
confidence: 99%